A SMART framework for HTA capability development: Lessons from India. Issue 1 (March 2020) - Mukherjee, Kanchan
Highlights: HTA capability development and use of HTA in Low and Middle income countries (LMICs) is very challenging. This commentary shares an innovative unique model for HTA capability development in India with learnings which would be useful for other low middle income countries in the Asian and African regions. The Indian model is based on a 'SMART' framework which bridges the gap between HTA researchers and HTA users. The principles used in the 'SMART' framework can be used to design and implement contextually relevant HTA capacity building programmes in a sustainable and cost effective manner in other LMICs.